Pengaruh Debt To Equity Rasio, Return On Asset Dan Total Asset Terhadap Price Earning Rasio Pada Perusahaan Sektor Makanan Dan Minuman Yang Terdaftar Di Bei Periode 2018-2022 - Jayadi, Irwan; Novida , Irma; Musharianto, Adi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
The aim of this research is to analyze empirical evidence using quantitative associative methods regarding the relationship between the influence of DER (X1), ROA (X2) and TA (X3) on PER (Y) in food and beverage sector companies listed on the Indonesia Stock Exchange for the period 2018- 2022.To find out the basis for decision making t isThe significance value is <0.05, there is an influence of variable X on variable YSignificance value > 0.05, there is no influence of variable X on variable YTo find out the basis for decision making in the F test as followsThe significance value is less or smaller than 0.05. Variable X influences variable Y simultaneouslyThe significance value is greater than 0.05, so variable X does not simultaneously influence variable Y.Based on the research results, it can be seen that the variables DER, ROA and TA have a simultaneous effect on PER. This proves that all independent variables in this study are able to explain their influence on financial performance.If a business has a lot of assets but cannot manage them well to generate proportional net profits, it can lead to a higher PER. Keywords: Debt to Equity Ratio, Return on Assets and Total Assets, Price Earning Ratio, Food and Beverage Sector Companies